2018
DOI: 10.21608/ejom.2018.4939
|View full text |Cite
|
Sign up to set email alerts
|

Work- Related Musculoskeletal Symptoms Among Nurse Staff in Ismailia, Egypt

Abstract: Introduction: Nursing career is considered one of the most physically laborious professions which are associated with high prevalence of work related musculoskeletal disorders (WMSDs). Although the latter is of major concern worldwide; limited epidemiological studies on WMSDs among nurses for referencing in Egypt. Aim of work:1) Assessing the prevalence of work related musculoskeletal symptoms (MSSs) among nurses in Suez Canal University Hospital and Ismailia General Hospital, 2) determining the associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Due to the diverse nature of their work, nurses are likely to be exposed to different risk factors (Attar, 2014), such as frequent torso twisting and bending and prolonged standing and lifting of patients. Several epidemiological studies have identified nursing as one of the occupations with the highest prevalence of work-related musculoskeletal disorders [WRMSDs] (Anap et al, 2013;Ellapen & Narsigan, 2014;Amer, 2018). In Ghana, nurses constitute 65% of the health workforce with a nurse to patient ratio of 1:22 and a nurse to population ratio of 1:750 (Ghana Health Service, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diverse nature of their work, nurses are likely to be exposed to different risk factors (Attar, 2014), such as frequent torso twisting and bending and prolonged standing and lifting of patients. Several epidemiological studies have identified nursing as one of the occupations with the highest prevalence of work-related musculoskeletal disorders [WRMSDs] (Anap et al, 2013;Ellapen & Narsigan, 2014;Amer, 2018). In Ghana, nurses constitute 65% of the health workforce with a nurse to patient ratio of 1:22 and a nurse to population ratio of 1:750 (Ghana Health Service, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…66 More so, Amer (2018) cross-sectional study revealed that there was a high frequency of WMSD among Egyptian nurses, and the lower back was mostly affected. 73 More evidence of lower back pain among nurses to convey the present study findings can also be found in the systematic review conducted by Pinar and Ali (2018). 74 The lower back was also the most affected body region in the systematic review and meta-analysis done by Saberipour et al (2019) among Iranian nurses.…”
Section: Years Of Employmentsupporting
confidence: 69%
“…The lower back was the most prevalent site (79.3%), and the researchers concluded that there is a high frequency of WMSD among Egyptian nurses, and the lower back is mostly affected. 73 Pinar and Ali (2018) also conducted a systematic review in the PubMed database to evaluate the prevalence of musculoskeletal disorders in nurses, and a total number of 34 articles were included in the analysis, and it was reported that MSD in nurses was limited in the last 12 months. The prevalence of MSD varied from 33% to 88%, and the most affected body region was the lower back, shoulder, neck, knees, wrist/hands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ever married nurses and nurses from rural areas had statistically significantly higher musculoskeletal complaints (p=0.001, (p=0.022) respectively (Results are not tabulated). Table (2) revealed that the prevalence of WMSDs accounted for 88% (No=176) of the study population who at least had one part of their body affected in the last 12 months, about 78.4% of them, their regular activities were affected and 92% of them experienced pain in the last week. Most of the studied nurses (68.5%) were complaining of low back pain in the last 12 months.…”
Section: Tablementioning
confidence: 99%